Corrosion of Carbon Steel by Shewanella chilikensis DC57 Under Thiosulphate and Nitrate Reducing Conditions - Salgar-Chaparro, Silvia J.; Tarazona, Johanna; Machuca, Laura L. (Frontiers in Bioengineering and Biotechnology, 2022)
Shewanella chilikensis DC57 is a bacterial strain isolated from a corrosion failure in a floating oil production system. Previous studies have indicated that this microorganism has potential to trigger corrosion of carbon steel through several metabolic pathways identified in its genome. In this study we evaluated the corrosion of carbon steel by S. chilikensis in the presence of thiosulphate or nitrate as terminal electron acceptors of the anaerobic respiration. Electrochemical response of carbon steel to the biofilm formation revealed differences in the corrosion process under the different electron acceptors conditions. Microscopic examination of the metal surface confirmed that S. chilikensis induced corrosion in both scenarios; however, in the presence of thiosulfate S. chilikensis triggered a higher pitting corrosion rate, whereas in presence of nitrate it promoted higher uniform corrosion. This study demonstrates the importance of understanding the metabolic versatility of microbes in order to assess the MIC risk of industrial facilities.